The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1021/jp806548p
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of Polyglutamine Aggregates Investigated via Molecular Dynamics Simulations

Abstract: Polyglutamine (polyQ) beta-stranded aggregates constitute the hallmark of Huntington disease. The disease is fully penetrant when Q residues are more than 36-40 ("disease threshold"). Here, based on a molecular dynamics study on polyQ helical structures of different shapes and oligomeric states, we suggest that the stability of the aggregates increases with the number of monomers, while it is rather insensitive to the number of Qs in each monomer. However, the stability of the single monomer does depend on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 82 publications
(163 reference statements)
4
33
0
Order By: Relevance
“…The time step size was 2 fs. Based on previous work, the SWNT atoms were modeled as uncharged Lennard-Jones particles using sp 2 carbon parameters [23,24] with a cross section of CC = 0.365 nm, and a depth of the potential well of CC = 0.465 kJ/mol. For the DPPC molecule, we used Berger's parameters [25].…”
Section: Methodsmentioning
confidence: 99%
“…The time step size was 2 fs. Based on previous work, the SWNT atoms were modeled as uncharged Lennard-Jones particles using sp 2 carbon parameters [23,24] with a cross section of CC = 0.365 nm, and a depth of the potential well of CC = 0.465 kJ/mol. For the DPPC molecule, we used Berger's parameters [25].…”
Section: Methodsmentioning
confidence: 99%
“…CE was investigated on other polypeptides (Tsemekhman et al 2007;Varga & Kovács 2005;Horvath et al 2004Horvath et al , 2005Improta & Barone 2004;Zhao & Wu 2002;Wieczorek & Dannenberg 2003;Viswanathan et al 2004;Scheiner & Kar 2005) with the application of first principle methods. However, here we provide a summary of the first study in which the presence and the importance of CE in the H-bonds of Qs side chains was verified with DFT approaches (Rossetti et al 2008). We performed first principles DFT-PBE (Benedek et al 2005;Morozov et al 2004;Perdew et al 1996) calculations on polyQ peptides of increasing complexity, assembled in parallel h β-sheets (Tsemekhman et al 2007;Koch et al 2005;Beke et al 2006;Perczel et al 2005).…”
Section: Hydrogen Bonding Cooperativity In Polyq β-Sheet Investigatedmentioning
confidence: 93%
“…Among these, several studies investigated the dependence of the structural stability of the circular β-helix, as well as of other possible structures, on the Q length (Stork et al 2005;Merlino et al 2006;Ogawa et al 2008;Rossetti et al 2008;Hajime et al 2008;Khare et al 2005), leading sometimes to conflicting views. For example classical MD studies showed that β-helices with three turns were unstable with circular geometries, being, instead, stable in a triangular β-helix shape.…”
Section: Structural Models Of Polyq Oligomers -Atomistic Simulationsmentioning
confidence: 99%
See 2 more Smart Citations